Black soldier fly larvae (BSFL) and their affinity for organic waste processing - Siddiqui, Shahida Anusha (Waste management (New York, N.Y.), 2022)
Copyright © 2022 The Authors. Published by Elsevier Ltd.. All rights reserved.